The Trans-Pacific Partnership’s Potential Economic Impact on Maine - deLutio, Catherine; Trostel, Philip (Maine Policy Review, 2016)
The Trans-Pacific Partnership (TPP) is a free-trade agreement (FTA) between 12 Pacific-Rim countries. If passed, it would be the largest FTA in which the United States participates. Catherine Reilly deLutio and Philip Trostel assess the potential impact of the TPP’s tariff reductions and quota increases on Maine’s economy. The results suggest that the TPP would likely generate slight increases in overall measures of Maine’s economy. The benefits would be relatively small and spread across the population.